Sibling empathy among preschoolers in China: analyzing emotional responses and family influences - Ye, Xiaolu; Ahmad, Nor Aniza; Burhanuddin, Nur Aimi Nasuha; Xie, Ruohan; Na, Meng (Frontiers Media SA, 2025)
Introduction: Empathy between siblings plays a pivotal role in early socio-emotional development, yet limited research has explored this construct within the context of Chinese preschool-aged children, particularly in light of China’s changing family structures. This study addresses this gap by examining the characteristics of sibling empathy and its associations with general empathy and sibling relationship quality. Methods: A total of 222 children aged 3 to 6 years from two-child families in Zhejiang Province, China, participated in this study. Sibling empathy was assessed using the newly developed Measurement of Sibling Empathy in Chinese Preschool Children (MSCP). The study examined differences in sibling empathy across age, gender, birth order, and sibling gender combinations (i.e., two boys, two girls, and one boy and one girl). A mediation model was tested to evaluate the role of sibling empathy in linking general empathy to sibling relationship quality. Results: Analysis revealed that younger children exhibited significantly lower empathy for sadness, and second-born children showed higher empathy for fear. Two-girl sibling pairs demonstrated greater empathy for anger than mixed-gender pairs. No significant gender differences were observed. General empathy was positively associated with both sibling empathy and sibling relationship quality. Structural Equation Modeling (SEM) indicated that sibling empathy significantly mediated the relationship between general empathy and sibling relationship quality. Discussion: The findings contribute to developmental and cultural theories of empathy by highlighting emotion-specific variations in sibling empathy and their implications for sibling dynamics in Chinese families. While the cross-sectional design and reliance on mother-reported data pose limitations, this study offers foundational insights and points toward targeted interventions to foster empathy and improve sibling relationships in early childhood.